Therapeutic Efficacy of Plant-Based Hydrogels in Burn Wound Healing: Focus on Satureja Montana L. and Origanum Vulgare L. - Demyashkin, Grigory A; Parshenkov, Mikhail A; Tokov, Alibek A; Sataieva , Tatiana P; Shevkoplyas, Ludmila A; Said, Bekeev S; Shamil, Gasanbekov N (Scripta Medica, 2025)
Background/Aim: Burn injuries present a critical issue for healthcare systems worldwide. They often lead to numerous complications, including persistent inflammation, impaired healing and heightened infection risks. The growing challenge of antibiotic resistance further complicates treatment, making bacterial infections harder to control and wound healing less effective. Existing treatment methods are often limited, highlighting the need for alternative approaches. Aim of this study was to analyse influence of hydrolate-based gels derived from Satureja montana L. and Origanum vulgare L. on the healing of burn wounds. Methods: New Zealand white rabbits (n = 25) with standardised Grade IIIa thermal burns were assigned to treatment groups receiving hydrolate-based gels (Satureja montana L. or Origanum vulgare L.), conventional therapy (Betadine (povidone-iodine) and Levomecol (methyluracil, chloramphenicol)), or no treatment. Inflammatory responses were tracked by collecting blood samples at the study’s begin, on day 3 and at one- and two-weeks post-burn, with subsequent ELISA analysis. Histological evaluation of tissue regeneration and inflammatory response was conducted using haematoxylin and eosin staining on days 3, 7 and 14. Results: By day 14, Satureja montana L. demonstrated the most effective reduction in interleukin 6 (IL-6), tumour necrosis factor alpha (TNF-α) and C-reactive protein (CRP) levels, nearing baseline values. This biochemical improvement correlated with histological findings, showing advanced epithelial regeneration, reduced inflammatory cell infiltration and clearer dermal-epidermal boundaries. The results highlight Satureja montana L. as the most effective treatment in both inflammation control and tissue repair compared to Origanum vulgare L. and conventional therapy. Conclusion: Hydrolate-based gels from Satureja montana L. and Origanum vulgare L. represent a promising option for adjunctive burn wound therapy. The Satureja montana L. group demonstrated significant improvements in inflammation control and tissue regeneration, while Origanum vulgare L. showed results comparable to standard therapy.